Still’s Disease–A Case of Diagnostic Dilemma - Razzak, Md Abdur; Rahman, Afsana; Rahman, Quazi Audry Arafat (Journal of Armed Forces Medical College, Bangladesh, 2020)
Still’s disease is an auto-inflammatory multisystem disease characterized by high spiking fever, salmon-colored rash that comes and goes, arthritis and other varieties of systemic manifestations. The puzzling fever and leukocytosis and high serum level of procalcitonin mistakenly may lead to diagnosis of severe bacterial infection or sepsis. But use of broad-spectrum antibiotic fails to improve the condition. It may mimic other multisystem autoimmune rheumatic diseases, but autoantibodies are negative. It may resemble the malignancies like leukemia and lymphoma, but lymph node biopsy and bone marrow study does not support. We have reported a case of Still’s disease in a 14-year-old young boy. Initially he presented like a viral illness, but high fever persisted for more than 4 weeks associated with body ache and skin rash withoutany arthritis. He had cervical lymphadenopathy, mild hepatosplenomegaly, pleural and pericardial effusion. He had persistent leukocytosis, high serum procalcitonin and high serum ferritin but low serum iron. Bacterial infection and sepsis were excluded, hematologic malignancy was ruled out by lymph node biopsy and bone marrow examination. There was no conclusive evidence of tuberculosis. Still a therapeutic trial was given but failed to produce any benefit. After exclusion of all the possible differentials and basing on diagnostic criteria he was diagnosed as a case of Still’s disease. With the use of steroid and immunosuppressive agent his condition improved dramatically and now he is leading a normal life. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 240-242